APOPTOSIS OF BLOOD CELLS IN GERIATRIC PATIENTS WITH ACUTE POISONINGS WITH PSYCHOPHARMACOLOGICAL DRUG - K. K. Ilyashenko; M. V. Belova; A. Y. Simonova; N. V. Borovkova; Y. V. Andreyev; M. M. Potskhveriya (Неотложная медицинская помощь, 2017)
We studied apoptosis of peripheral blood cells in 47 patients older than 60 years with varying course and outcome of acute poisoning with psychopharmacological drugs. It is shown that a control group of volunteers of the same age should be formed for an objective assessment of these disturbances. We revealed deviation of apoptotic parameters from the control group values. However, we failed to specify its information value for the prognosis and disease outcome